Performimg Education: The Utopian Potential of Creative Peer-to-peer Sexual Health Education for Queer Youth - Ligate, Ashling (University of Waterloo, 2012)
In this cultural moment, young queers are struggling to imagine themselves and find community. A significant component of enabling a youth's self-discovery is providing access to inclusive and culturally-relevant education about their bodies, especially as it relates to sexual health. Current models of instruction are limited. Institutional learning environments may rely on materials that are overtly or subtly homophobic (for example, speaking only of heterosexual relationships outside of the small section or chapter on other forms of sexual orientation). If a youth is lucky enough to encounter materials that strive to be more inclusive, the communication method may be dry and purely factual, leaving the youth to attempt to translate useful information into their daily life. This project addresses the gap in sexual health education for queer youth. I argue for the potential of using disidentificatory performance as a medium through which to build a self-sufficient commons for young queer people. In order to first identify the markers of this method of communication, I draw upon the work of Jose Esteban Munoz, a queer theorist and performance studies scholar. I conducted a critical content analysis of the fifth episode of the online video series called Heavy Petting and considered whether or not it could be considered an example of disidentificatory performance used for sexual health education. In my analysis of Heavy Petting, four themes arose, each of which related to things that are needed in order for a young queer commons to be self-sufficient: (1) tools for queering toxic tropes; (2) communication methods that allow for dissensus; (3) stylish politics grounded in a subversive aesthetic; and (4) role models and educators who will help create an intimate queerworld, in the words of Munoz. The results of my findings indicate that the Heavy Petting video is an example of disidentificatory performance, in that it satisfies the three criteria that I name as constitutive of the genre. This suggests that such peer-to-peer educational projects do indeed hold the potential to support commons building among young queer people.
The Independent Studies program closed in 2016. This thesis was one of 25 accepted by Library for long-term preservation and presentation in UWSpace.
Keywords: sexual health education; queer youth; instituitional learning models; inclusivity; homophobic impact; disidentificatory performance